ELISA-based serological survey of Mycoplasma bovis in cattle in three local government areas in Adamawa State, Nigeria (Journal of Advanced Veterinary and Animal Research, 2015)
A serological survey for the detection of antibodies to Mycoplasma bovis was conducted in Adamawa State, Nigeria during the year 2012. A total of 400 serum samples were collected from three local government areas (LGA) namely Yola (n=140), Mubi (n=130) and Ganye (n=130), and the samples were examined for the presence of M. bovis antibodies using BIO-X M. bovis antibody ELISA Kit. The overall seroprevalence of M. bovis was recorded as 19.5% (n=78/400). The highest seroprevalence was recorded in Ganye LGA (27.7%; n=36/130), followed by Yola LGA (20.0%; n=28/140) and Mubi LGA (10.8%; n=14/130). The cattle aging